Facultative heterospecific brood parasitism among the clutches and broods of duck species breeding in South Bohemia, Czech Republic - Musil, Petr; Musilová, Zuzana; Poláková, Klára (Wildfowl, 2017)
Heterospecific brood parasitism (HBP) frequently occurs in waterfowl, though much less often than conspecific brood parasitism. In this study, we assess the rate of HBP among clutches and broods of five sympatric breeding duck species: Gadwall Anas strepera, Mallard Anas platyrhynchos, Red-crested Pochard Netta rufina, Common Pochard Aythya ferina and Tufted Duck Aythya fuligula from nest and brood surveys carried out in theÂ TÅ™eboÅˆ BiosphereÂ Reserve and surrounding area (South Bohemia, Czech Republic) in 2006â€“2015 inclusive. Assessment of 2,323 clutches and 3,056 broods found a higher rate of HBP in clutches than in broods. The rate of HBP in the broods of host birds did not increase with the rate of HBP in host clutches for the five species investigated. The highest proportion of brood parasitism recorded was among Red-crested Pochard. Tufted Duck showed the lowest difference in the HBP rate between clutches and broods; Mallard the highest. From the parasitising femaleâ€™s perspective, the rate of HBP in clutches increased with the rate of HBP in broods for each species investigated. We can conclude that the choice of host affects the success of HBP (i.e. the frequency of HBP in clutches vs. rate of HBP in broods), and that this can differ between the five species included in the study. Tufted Duck seems to be the most suitable host species as well as the most successful parasite.